Characteristic Analysis of the MS6.8 Luding Earthquake Sequence in Sichuan, China, on Sept. 5, 2022 - Min Zhao; Feng Long; Yue Gong; Fang Du (Journal of Risk Analysis and Crisis Response (JRACR), 2024)
The MS6.8 earthquake occurred in Luding County, Ganzi Prefecture, Sichuan Province, China at 12:52 p.m. on Sept. 5, 2022, is preliminarily analyzed in terms of regional tectonics, historical earthquakes, sequence characteristics and focal mechanism solutions. The results show that: 1) The magnitude difference ΔM between the main shock and the maximum aftershock, the energy ratio ER of the main shock to the aftershocks, the p-value and the estimated Mmax-value indicate that the MS6.8 Luding earthquake sequence can be divided into the main shock-aftershock type (MAT). 2) The spatial distribution of the aftershocks, their corresponding b-value and expected maximum magnitude are obviously segmented, which reflect the complexity of the seismogenic tectonics. 3) According to the focal mechanisms obtained from the HASH program, the geometry distribution of the sequence, and the relationship between the sequence and the nearby faults, it can be inferred that the Moxi fault segment of the Xianshuihe fault zone is the seismogenic tectonics of the MS6.8 Luding earthquake sequence.